Climate risk and bank capital structure - Bakkar, Yassine (Journal of Financial Stability, 2026)
This paper examines whether climate risk affects the dynamics of banks’ regulatory capital adjustments, based on a large panel of European banks over the 2006–2021 period. Using a dynamic partial adjustment model, we find that climate-exposed banks hold higher capital adequacy ratios and adjust faster toward their optimal capital structure, particularly when exposed to transition risk and post-COP21. Climate risk also induces asymmetric adjustment behaviours. Deleveraging occurs through risk-weighted asset reallocation toward safer exposures, without asset liquidation or lending cuts. While leveraging operates through risk-weighted asset expansion, without reducing equity growth. However, pre-COP21, deleveraging is primarily achieved through lending contraction, whereas leveraging relies mainly on asset expansion. Our findings highlight the policy relevance of climate risk for prudential supervision and bank capital regulation.